16Oxygen irradiation enhances cued fear memory in B6D2F1 mice. (November 2015) - Raber, Jacob; Marzulla, Tessa; Kronenberg, Amy; Turker, Mitchell S.
Abstract: The space radiation environment includes energetic charged particles that may impact cognitive performance. We assessed the effects of 16 O ion irradiation on cognitive performance of C57BL/6J × DBA/2J F1 (B6D2F1) mice at OHSU (Portland, OR) one month following irradiation at Brookhaven National Laboratory (BNL, Upton, NY). Hippocampus-dependent contextual fear memory and hippocampus-independent cued fear memory of B6D2F1 mice were tested. 16 O ion exposure enhanced cued fear memory. This effect showed a bell-shaped dose response curve. Cued fear memory was significantly stronger in mice irradiated with 16 O ions at a dose of 0.4 or 0.8 Gy than in sham-irradiated mice or following irradiation at 1.6 Gy. In contrast to cued fear memory, contextual fear memory was not affected following 16 O ion irradiation at the doses used in this study. These data indicate that the amygdala might be particularly susceptible to effects of 16 O ion exposure.